Fluorination of closo-dodecaheteroborane anions: new superweak anions and nonclassical metal carbonyls: a theoretical study - Lupinetti, Anthony John, author; Strauss, Steve, advisor (Colorado State University. Libraries, 1999)
The first part of this dissertation details the synthesis and characterization of a series of very weakly basic or superweak anions with the form. EB11H11–nFn–(E = CH, As, Sb, Bi). Reaction of the unfluorinated anions with liquid anhydrous hydrogen fluoride (LAHF) at temperatures below 230°C proceeded in a stepwise manner with excellent compositional (n = 1–4) and isomeric purity for CB11H12–: 12-CB11H11F–,7,12-CB11H10F2–, 7,9,12-CB11lH9F3–, and 7,9,10,12-CB11H8F4–. Mixtures resulted at higher temperature. The target compound 7—12-CB11H6F6– was isolated after separation using size exclusion chromatography. The EB11H11– clusters reacted differently; substitution occurred at the antipodal (AsB11H11–) and lower-belt positions (E = As, Sb, Bi). The N-fluoro reagent F-TEDA-BF4 also fluorinated CB11H12– (n = 1–6) but produced isomeric mixtures. The NMR data of CB11H12–nFn– were used to provide insight about electronic structure and substitution patterns. In the second part, high v(CO) carbonyl complexes were examined by computational methods, and a definition for nonclassical metal carbonyls was proposed. It was found that the effect of a positive charge on a carbonyl ligand serves to make the C–O bonds less polar in X+–CO complexes and more polar in CO–X+ complexes. Predicted bond dissociation energies (BDEs), geometries, and electronic structures were calculated for group-11 and group-12, d10 M(CO)n+/2+ (n = 1–6) complexes at the MP2, CCSD(T), BP86, and B3LYP levels of theory. Calculated CCSD(T)/I//MP2/I BDEs were in good agreement with experimental results, while DFT methods performed poorly for n = 1, 2. Ion-dipole coulombic attractions were found to be important in the complexes. Sequential BDEs for the group-12 complexes were more endothermic those of the group-11 complexes. Finally, the behavior of metal carbonyl complexes perturbed in one of two was monitored: adding two fluoride ions to M(CO)nx (n = 2, 3; x = –1 to +2) cations and compressing the M–C bond of M(CO)n+ (n = 1, 2) complexes. These perturbations produced two responses in the M–C and C–O bonds and further supported the need for two classes of metal carbonyl complexes—classical and nonclassical.
Keywords: chemistry; physical chemistry; inorganic chemistry